Effects of education on low-phosphate diet and phosphate binder intake to control serum phosphate among maintenance hemodialysis patients: A randomized controlled trial - Eunsoo Lim; Sunah Hyun; Jae Myeong Lee; Seirhan Kim; Min-Jeong Lee; Sun-Mi Lee; Ye-Sung Oh; Inwhee Park; Gyu-Tae Shin; Heungsoo Kim; Donald E. Morisky; Jong Cheol Jeong (The Korean Society of Nephrology, 2018)
Background : For phosphate control, patient education is essential due to the limited clearance of phosphate by dialysis. However, well-designed randomized controlled trials about dietary and phosphate binder education have been scarce. Methods : We enrolled maintenance hemodialysis patients and randomized them into an education group (n = 48) or a control group (n = 22). We assessed the patients' drug compliance and their knowledge about the phosphate binder using a questionnaire. Results : The primary goal was to increase the number of patients who reached a calcium-phosphorus product of lower than 55. In the education group, 36 (75.0%) patients achieved the primary goal, as compared with 16 (72.7%) in the control group (P = 0.430). The education increased the proportion of patients who properly took the phosphate binder (22.9% vs. 3.5%, P = 0.087), but not to statistical significance. Education did not affect the amount of dietary phosphate intake per body weight (education vs. control: -1.18 ± 3.54 vs. -0.88 ± 2.04 mg/kg, P = 0.851). However, the dietary phosphate-to-protein ratio tended to be lower in the education group (-0.64 ± 2.04 vs. 0.65 ± 3.55, P = 0.193). The education on phosphate restriction affected neither the Patient-Generated Subjective Global Assessment score (0.17 ± 4.58 vs. -0.86 ± 3.86, P = 0.363) nor the level of dietary protein intake (-0.03 ± 0.33 vs. -0.09 ± 0.18, P = 0.569). Conclusion : Education did not affect the calcium-phosphate product. Education on the proper timing of phosphate binder intake and the dietary phosphate-to-protein ratio showed marginal efficacy.